Influence of gestational diabetes mellitus on the cardiovascular system and its underlying mechanisms - Zhang, Ze; Zhang, Yumeng; Huang, Shuai; Li, Min; Li, Lingjun; Qi, Linglu; He, Yun; Xu, Zhice; Tang, Jiaqi (Frontiers in Endocrinology, 2025)
Gestational diabetes mellitus (GDM) is one of the most common endocrine-related complications during pregnancy, and its prevalence has increased over the past three decades. GDM adversely affects the maternal cardiovascular system, umbilical–placental blood perfusion, and fetal blood flow. We conducted a comprehensive literature search and systematically evaluated and synthesized cardiovascular changes in the mothers, umbilical–placental circulation, and the progeny following exposure to GDM. Multiple pathophysiological mechanisms underlying cardiovascular alteration were investigated, including endothelial dysfunction, insulin resistance, oxidative stress, ion channel abnormalities, inflammation, angiogenic imbalance, and epigenetic modifications. These findings provide valuable insights for developing early intervention strategies and therapeutic approaches to mitigating cardiovascular risks in both mothers and offspring following GDM exposure.